Morphology of ammonium perchlorate in the presence of ethylene glycol as an additive: a first principle study - Khan, Md Abdul Shafeeuulla; Vijayalakshmi, R.; Singh, Avtar; Nandi, Amiya Kumar; Talawar, M. B. (Crystengcomm, 2019)
Ammonium perchlorate (AP) is an extensively used crystalline oxidizer in high energy materials and their compositions. A desired morphology of AP is crucial for the high burn rates of solid propellants. We have examined the habit modification of AP crystals in the absence and presence of ethylene glycol as an impurity by means of important parameters such as interaction and surface energies to predict the resultant morphology. On the basis of first principles density functional theory (DFT) calculations of the binding and surface energies before and after the adsorption of the surface-capping agent (ethylene glycol) on the AP surfaces, we have shown that the relative stability of all the important surfaces (100), (101), (011), (001) and (210) rationalize the habit modification of AP crystals. In accordance with the surface energy calculations, the stability order of the five crystallographic surfaces of AP was found to be (001) > (210) > (101) > (100) > (011) in the absence of additive molecules, i.e., in the clean surfaces. This result is in concurrence with the fact that AP crystals richly contain (001) planes when grown in the absence of an additive. The computational methodology applied for the determination of surface energies was found to be reliable as it has well reproduced the stability trend of AP surfaces. However, the trend, (210) > (001) > (101) > (011) > (100), was observed when these surfaces were capped with a known additive molecule, i.e., ethylene glycol. The crystal habit of AP in the presence of ethylene glycol is such that the intensity of the lattice plane (2 1 0) of the modified AP was remarkably high leading to the shape of hexahedral, which is in excellent agreement with the experimental results. A linear fit correlation was also observed between surface energies and interaction energy values for the additive adsorbed AP surfaces.

Examining the compatibility of energetic plasticizer DNDA-5 with energetic binders - Vijayalakshmi, R.; Agawane, N. T.; Talawar, M. B.; Khan, Md Abdul Shafeeuulla (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
The requirement of developing energetic binders with suitable energetic plasticizers is to enhance the mechanical properties and to reduce glass transition temperature of propellant and explosive formulations. Compatibility of energetic plasticizer 2,4-dinitro-2,4-diazapentane (DNDA-5) with four different energetic binders viz. poly glycidyl nitrate (PGN), poly(3-nitratomethyl-3-methyloxetane) (PLN), glycidyl azide polymer (GAP) and tetra functional glycidyl azide polymer (t-GAP) was studied by using differential scanning calorimeter (DSC) and density functional theory (DFT) methods. Results obtained for the pure binder was compared with the results obtained for binder/plasticizer blend in the parameters of decomposition temperature and the format of the peak which indicated the compatibility or incompatibility of DNDA-5 with the studied binders. Glass transition temperatures of all these blends were determined by low temperature DSC and showed desirable lowering of glass transition temperature with single peak in the case of PLN. The proposed energetic plasticizer DNDA-5 has displayed its compatibility with three binders PGN, PLN and GAP employing thermal techniques. DNDA-5 has been found as incompatible when it is mixed with t-GAP. The predicted relative trend of interaction energies between plasticizer and binder has provided concurrence to results drawn from thermal studies.
Keywords: Computational study; DNDA-5; Glass transition temperature; plasticizing effect; thermal